The persuasive communication of Instagram influencers to promote tourism in the Riviera Maya - Belén Rodríguez-Hidalgo, Alma; Sixto-García, José; Tamayo-Salcedo, Ana Leticia (Frontiers in Communication, 2025)
IntroductionDestination management organizations are using influencer marketing to implement alliances with influencers to actively stimulate tourist visits. This study analyzes the tourism promotion strategy employed by the content creators hired by the Quintana Roo Tourism Promotion Council to promote the Riviera Maya in Mexico.MethodsUsing a mixed methodology approach and drawing on the functionalist paradigm of communication, the content of the publications is examined.Results and discussionThe results show that the physical appearance and communication skills of influencers have an impact on tourists’ travel intentions. Moreover, the analysis concludes that the motivation conveyed by the influencer shapes the reception of the message.